2023
DOI: 10.3389/fmicb.2023.1138914
|View full text |Cite
|
Sign up to set email alerts
|

Association of residual feed intake with intestinal microbiome and metabolome in laying period of ducks

Abstract: IntroductionResidual feed intake (RFI) is a indicator to evaluate animal feed. This experiment was explored to study the relationship between intestinal microbiome and metabolome of ducks with different residual feed intake during laying period.MethodsA total of 300 Shaoxing ducks aged 42 weeks were randomly selected and fed a diet of 60 d. At the end of the trial, 20 samples were selected according to the phenotype of RFI and divided into two groups (HRFI and LRFI). The cecal microbiota composition was explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
1
0
0
Order By: Relevance
“…The quality of eggs plays a crucial role for both producers and consumers during storage, processing, and consumption processes. Consistent with the findings of Sun [39] , our study also found no significant differences between the high and low RFI groups in terms of ESI, ESC, and EW. Therefore, selective breeding for RFI during the late stage of egg production is possible, as it can reduce feed consumption without significantly affecting egg quality.…”
Section: Discussionsupporting
confidence: 92%
“…The quality of eggs plays a crucial role for both producers and consumers during storage, processing, and consumption processes. Consistent with the findings of Sun [39] , our study also found no significant differences between the high and low RFI groups in terms of ESI, ESC, and EW. Therefore, selective breeding for RFI during the late stage of egg production is possible, as it can reduce feed consumption without significantly affecting egg quality.…”
Section: Discussionsupporting
confidence: 92%